GROWTH OF THE INTERNET AND KNOWLEDGE GRAPH IN EMERGING ECONOMIES STUDY (International journal of artificial intelligence, 2024)
Distributed communications network with no single central point – dates back to the days of the telegraph; however, the real research base was conducted by the US Advanced Research Projects Agency (ARPA) in 1968 to develop a series of protocols or procedures that would allow computers to communicate with each other over a packet network. This set of protocols, published in 1974, is called the Transmission Control Protocol/Internet Protocol (TCP/IP) and is the computing foundation of the Internet.